Prevalence of common conditions and associated mortalities of dogs treated at the small animal clinic, Makerere University, Kampala, Uganda - James Okwee-Acai; Benard Agwai; Patrick Mawadri; Christine Kesiime; Methodius Tubihemukama; Joseph Kungu; Benard Odur (BMC Veterinary Research)
Abstract Background In developing countries such as Uganda, domestic dogs suffer high burdens of infectious diseases often with high mortalities. Surveillance data on the common diseases and associated mortalities is however scanty. We thus, present results of a retrospective study of common clinical conditions and mortalities of dogs brought for treatment at the small animal clinic, Makerere University, Kampala, Uganda. Methods We analysed data from the case records register of the clinic from January 2021-December, 2022. Descriptive statistics were generated using the frequency functions of R (R-4.3.3 for Windows®). Records were reviewed for all 650 cases presented at the clinic except those presented for routine care services like vaccination and grooming. Results Up to 51% of the dogs were female, mostly (56%) under two years old. The Alsatian (30.7%) and mongrel (22.7%) were the commonest breeds. Cases were recorded as: elective surgeries (29.2%), parvovirus infection (13.9%), skin infections (09.7%), canine babesiosis (6.9%), fractures (6.0%) and neoplasms (6%); mainly transmissible venereal tumour (TVT). Some (3.4%) dogs developed post-operative complications, while 4.8% were euthanized and 12% died during treatment. Of the dogs that died, 50% were parvovirus infection cases while other conditions included babesiosis (13%), poisoning (7.8%), pyometra (7.8%) and liver dysfunction (5.1%). Conclusion We impute that parvovirus infection and other preventable diseases were the most frequent reasons for morbidity and mortality of especially puppies in Uganda. This points to the need for epidemiologic surveillance of dog diseases and community sensitisation for improved control of dog diseases.